The Risk of Developing Aphasia and Exposure to Air Pollution in Taiwan - Jinyi Hung; Pei-Chun Lin; Chiu-Ying Chen; Stella Chin-Shaw Tsai; Ruey-Hwang Chou; Cheng-Li Lin; Der-Yang Cho; Ching-Liang Hsieh; Chang-Yin Lee; Kuang-Hsi Chang; Yi-Chao Hsu; Tai-Lin Huang (Atmosphere)
(1) Background: The relationship between air pollution and the risk of developing aphasia is still unclear. We aimed to evaluate air pollution exposure as a risk factor for developing aphasia in Taiwan. (2) Methods: This retrospective population-based cohort study used the Longitudinal Generation Tracking Database (LGTD) and the Taiwan Air Quality Monitoring Database (TAQMD). The incidence rate ratio (IRR) and adjusted hazard ratio (aHR) were calculated to examine the association between aphasia and exposure to six air pollutants: sulfur oxide (SO2), carbon monoxide (CO), nitric oxide (NO), nitrogen oxide (NOx), and particulate matter (PM2.5, PM10) from 2003 to 2017. (3) Results: The incidence rate ratio (IRR) of aphasia showed that individuals with high levels of SO2, CO, and NO were at a higher risk of developing aphasia. Increased exposure to airborne particulate matter (PM2.5 and PM10) also increased the risk of developing aphasia. The adjusted HRs of the aphasia risk were statistically significant for all the air pollutants at higher concentrations. (4) Conclusions: Individuals exposed to ambient air pollutants have a significantly higher risk of developing aphasia. The greater the exposure to airborne particulate matter and gaseous pollutants, the more likely individuals are to develop aphasia.